Penggalangan Civic Literacy Melalui Organisasi Kemahasiswaan dan Pandangan mengenai Tantangan Demokrasi di Indonesia - Rayi Retriananda Maulana; Arry Bainus Bainus (DEMOKRASI: Jurnal Ilmu Pemerintahan, 2022)
This research is aimed at describing civic literacy rasing among university students involved in student organizations. The research objective is to reveal their views on democratic practices in Indonesia, particularly through the moment of the 2019 elections. The research is conducted by a qualitative method, specifically by phenomenological approaches such as interviews, observation, and collecting documents. The result of the study shows that a positive outlook has been perceived by the students with regard to the 2019 election as a scheme of political leadership recruitment in Indonesia. The result also shows that according to the student perceptions, the challenge of the practice of democracy in Indonesia through the election voting has been contested by the impact of digital culture. Within this context, the respondents’ knowledge about civic literacy and their political participation have been also affected by the upscaling digital practices, therefore it has been a future challenge for Indonesian democracy in next the future.